Did the Australian Jobkeeper Program Save Jobs by Subsidizing Temporary Layoffs? - Jeff Borland; Jennifer Hunt (Institute of Labor Economics (IZA), 2021)
We analyze the JobKeeper lump-sum wage subsidy introduced by the Australian government in response to the COVID-19 pandemic, paying particular attention to the role of temporary layoffs in saving jobs. Although temporary layoffs were widely used, we find that recalls of workers on temporary layoff played only a small role in the early recovery. This suggests either that temporary layoffs were very long, or that many workers on temporary layoffs were never recalled.
Keywords: J08; J20; 330; COVID-19; JobKeeper; wage subsidy; temporary layoffs